Digital transformation : information systems governance - Leignel, Jean-Louis.; Ungaro, Thierry; Staar, Adrien (London : ISTE, Ltd. ; Hoboken, NJ : Wiley, 2016)
The main aim of this book is to offer companies a simple and practical method to assess their maturity in the Governance Information System, so that they are in working order to face the challenges of Digital Transformation. How can companies effectively manage their investment in IT systems and make the most of their development'
5.4. Vector 4: alignment of the IT organization with respect to business processes5.4.1. Issues of this vector in the digital transformation; 5.4.2. Issues of the vector in terms of contribution to IS governance; 5.4.3. Best practices associated with the vector and measurement of the company's maturity level in the vector; 5.5. Vector 5: IS-related budgetary management and costs control promoting transparency; 5.5.1. Vector challenges in the digital transformation; 5.5.2. Issues of the vector in terms of contribution to IS governance.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Information technology -- Management; Technologie de l'information -- Gestion; COMPUTERS -- Information Technology; COMPUTERS -- Computer Literacy; COMPUTERS -- Computer Science; COMPUTERS -- Data Processing; COMPUTERS -- Hardware -- General; COMPUTERS -- Machine Theory; COMPUTERS -- Reference; Information technology -- Management